ANALISIS KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI PERKEMBANGAN MODEL ATOM MELALUI PEMBELAJARAN BERBASIS MASALAH (PBL) - Afriyanto, Afriyanto; Haetami, Aceng; Marhadi, Muh. Alim (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2021)
Research has been carried out that aims to analyze the critical thinking skills of students and find out the most dominant indicators of critical thinking skills of students after the implementation of the Problem Based Learning model. This research was conducted in class X IPA SMA Negeri 1 Wawonii Utara. The sample of this study was 21 students of class X science. This research method uses quantitative descriptive. The instruments used in this study are description tests and observation sheets. The results of data analysis show that the achievement of students' critical thinking skills in general has been well achieved. The most dominant indicators of students' critical thinking skills in the high, medium and low groups are the same, namely the interpretation indicators and analysis indicators.